AKUNTANSI, BUDAYA, DAN AGAMA HINDU: SEBUAH TINJAUAN NARATIF - I Made Dwi Hita Darmawan; I Gusti Ngurah Agung Panji Tresna (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
This research aims to analyze and understand the relationship between accounting and Balinese Hindu culture through a descriptive qualitative approach using the narrative review method. This research method is used to explore phenomena that occur in the context of Balinese Hindu culture with a focus on accounting practices. The results of data analysis show that the relationship between accounting and Balinese Hindu culture influences each other. Balinese Hindu culture that is rich with traditions, rites, and spiritual values has a significant impact on the accounting practices that exist within its society. Accounting practices in Balinese Hindu culture reflect the beliefs and values of the community, such as the concepts of justice, ethics, and social responsibility. The novelty of this research lies in providing a better understanding of the influence of Balinese Hindu culture on accounting practices, so that it can be used as a basis for the development of more contextualized and sustainable accounting theories and practices within the culture.